Vocabulario de morfoloxía, anatomía e citoloxía veterinaria: (galego-español-inglés) [EN, ES, GL] - Rodríguez Río, Xusto A. (Universidad de Santiago de Compostela, 2008)
Keywords: Ciencia; Ciencias da saúde; Ciencias médicas; Dicionario terminolóxico; Español (Lingua); Galego (Lingua); Inglés (Lingua); Terminoloxía; Vocabulario; Zooloxía

Fleischner Society: Glossary of Terms for Thoracic Imaging [EN] - Hansell, David M.; Bankier, Alexander A.; MacMahon, Heber; McLoud, Theresa C.; Müller, Nestor L.; Remy, Jacques (Radiology, 2008)
Members of the Fleischner Society compiled a glossary of terms for thoracic imaging that replaces previous glossaries published in 1984 and 1996 for thoracic radiography and computed tomography (CT), respectively. The need to update the previous versions came from the recognition that new words have emerged, others have become obsolete, and the meaning of some terms has changed. Brief descriptions of some diseases are included, and pictorial examples (chest radiographs and CT scans) are provided for the majority of terms. © RSNA, 2008
Keywords: Ciencia; Ciencias da saúde; Ciencias médicas; Dicionario terminolóxico; Glosario; Inglés (Lingua); Terminoloxía

Vocabulario de medicina [EN, ES, GL, PT] - Casas García, María; Miguélez Ferreiro, Sonia; Pena Álvarez, Carolina; Pereira Fernández, Iria; Rubín Barrenechea, Adriana; Sánchez Trigo, Sabela; Vázquez Vicente, Xoana María; Vidal Castiñeira, Isabel; Rodríguez Río, Xusto A (Universidade de Santiago de Compostela. Servizo de Publicacións e Intercambio Científico, 2008)
Keywords: Ciencia; Ciencias da saúde; Ciencias médicas; Dicionario terminolóxico; Español (Lingua); Galego (Lingua); Inglés (Lingua); Portugués (Lingua); Terminoloxía; Vocabulario

A Dictionary of Psychology [EN] - Colman, Andrew M. (Oxford University Press, 2008)
Keywords: Dicionario terminolóxico; Inglés (Lingua); Psicoloxía; Terminoloxía

Glosario de termos de prevención, saúde e ambiente laborais [GL] - Gabinete Técnico de Saúde Laboral (Confederación Intersindical Galega, 2008)
Keywords: Ciencia; Ciencias da saúde; Ciencias médicas; Dicionario terminolóxico; Galego (Lingua); Glosario; Terminoloxía

Profesionaliza a túa lingua: fisioterapia [ES, GL] - Pereiro Felípez, Mª del Carmen; Pérez Vázquez, Libia; Precedo Estraviz, Patricia; Seoane Bouzas, Nuria (Servizo de Normalización Lingüística Universidade da Coruña, 2008)
Keywords: Ciencia; Ciencias da saúde; Ciencias médicas; Dicionario terminolóxico; Español (Lingua); Galego (Lingua); Terminoloxía